2021
DOI: 10.1186/s12903-021-01784-w
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of conventional versus electronic cigarette use on treatment outcomes of peri-implant disease

Abstract: Aim To compare changes in clinical periodontal parameters (gingival consistency, colour, BOP, PI, PD) and changes of salivary inflammatory biomarkers (IL-1 β, IL-6, MMP-8, TNF- α and TIMP-1 between conventional, electronic cigarette smokers and non-smokers after peri-implant treatment. Methods Study participants were grouped into three groups (i) Conventional cigarette smokers (ii) Electronic cigarette smokers and (iii) non-smokers respectively. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 45 publications
1
11
0
5
Order By: Relevance
“…A typical feature of periodontal disease associated with tobacco smoking is a greater destruction of the supporting tissues of the teeth with clinical attachment loss [ 67 ]. Many studies, reported in this review, agreed with this; in fact, Mokeem et al, BinShabaib et al, Ibraheem et al and Fangxi Xu et al described that CS had the worst CAL values compared to NS [ 50 , 54 , 58 , 65 ]. Aldakheel et al also came to the same conclusion, reporting higher CAL values in CS, E-Cigs and NS with periodontitis compared to NS without periodontitis [ 57 ].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A typical feature of periodontal disease associated with tobacco smoking is a greater destruction of the supporting tissues of the teeth with clinical attachment loss [ 67 ]. Many studies, reported in this review, agreed with this; in fact, Mokeem et al, BinShabaib et al, Ibraheem et al and Fangxi Xu et al described that CS had the worst CAL values compared to NS [ 50 , 54 , 58 , 65 ]. Aldakheel et al also came to the same conclusion, reporting higher CAL values in CS, E-Cigs and NS with periodontitis compared to NS without periodontitis [ 57 ].…”
Section: Discussionsupporting
confidence: 76%
“…Regarding plaque accumulation, many authors reported higher PI values in CS and E-Cigs compared to NS [ 53 , 58 , 59 , 64 ]. In more detail, Vohra et al reported that CS had the worst PI values compared to E-Cigs and NS [ 55 ]; conversely, AlJasser et al found that NS had worse plaque conditions than E-Cigs and CS [ 65 ]. Mokeem et al also found higher, although not significantly different, PI values around natural teeth in CS than E-Cigs and in E-Cigs than in, otherwise ArRejaie et al did not find any differences in PI around dental implants between CS and E-Cigs [ 50 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is certainly also in the interest of implant manufacturers, so that financial support for research would be guaranteed. Nevertheless, the results of this Scoping Review revealed only 1 clinical trial focusing on saliva and possible association with peri-implantitis ( 21 ). In addition, dentistry could become the door-opener for routine diagnostics in medicine, e.g., assessment of glucose concentration in diabetes patients ( 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review concluded that smoking yielded more bone loss than any type of implant surface 124 . Recent longitudinal and cross‐sectional studies have demonstrated the detrimental impact of tobacco smoking on the stability of peri‐implant tissues 94,125–130 . During up to 22 years of following 4247 patients with 10 871 implants, heavy cigarette smoking (>10 pack years) almost doubled the risk for implant failure defined as removal for any reason (HR = 1.81) 94 .…”
Section: Impact Of Systemic Driversmentioning
confidence: 99%